Quality Assessment, Functional Potentials, and Safety Evaluation of Stored Egyptian Honey as an Environmental Pollution Bioindicator. (25th September 2020) - Hamad, Gamal M.; Hafez, Elsayed E.; Abdelmotilib, Neveen M.; Abdel‐Hmeed, Khaled M.; Ali, Safwat H.; Darwish, Amira M.G.
Abstract: Egyptian honeys are distinguished by their variety, properties, and therapeutic applications. The aim of the present study was to evaluate the quality and the functional and safety characteristics of Egyptian honey as a sensitive environmental bioindicator collected from 9 different locations in Egypt that were exposed to various air pollution sources, either stationary, mobile, or area sources, and stored for 6 mo at ambient temperature (22 ± 2 °C) compared with Codex Alimentarius international standards. Physicochemical properties, sugar profile via high performance liquid chromatography, functional potentials (antioxidant and antimicrobial), and safety parameters (microbiological quality, aflatoxins, and heavy metal pollutants) were assessed. The results revealed that honey obtained from Shabshir Hessa, El Gharbia Governorate (GSH‐1), showed the best quality with the highest monosaccharide and phenolic and flavonoid content (73.07%, 363.07, and 15.33 mg/g, respectively) and clear of biotic and abiotic contaminants, reflecting good hygienic, environmental conditions and apiarian practices. The other 8 honey samples reflected inferior quality in physicochemical parameters either of low monosaccharide content (40.46–50.25%), high hydroxymethylfurfural (HMF) values as in Borg El‐Arab Industrial Zone, Alexandria Governorate (BAI‐9), and Nubaria Desert Road, Alexandria Governorate (NDR‐4; 50.83 and 48.25 mg/kg), or of high acidity as in Agricultural Road, El Gharbia Governorate (GAR‐3), and NDR‐4 (74.72 and 68.47 mEq/kg) attributable to contaminated locations (fermentations) or thermal treatment (HMF). Furthermore, safety assessment revealed that coliform counts exceeded 2.5 log10 cfu/g in 6 samples—Chemicals Company, Kafr El Zayyat Governorate (KZC‐2); GAR‐3; NDR‐4; Mansoura Fertilizer Talkha Company, Daqahlia Governorate (MFT‐5); Gharbaniyat Cement Company, Beheira Governorate; and BAI‐9—and the highest counts of yeast and molds in Abees Ceramic Company, Alexandria Governorate (3.72 log10 cfu/g), which was reflected in its total aflatoxins (679.83 μg/kg). Samples MFT‐5; GAR‐3; Kafr El‐Sheikh Petroleum Company, Kafr El‐Sheikh Governorate; and KZC‐2 exceeded the lead permissible limit (0.75, 0.61, 0.57, and 0.51 mg/kg, respectively) as a result of inferior hygienic quality and the negative effects of environmental pollutants. The results ring alarm bells about how we should take substantial steps toward stringent standards for quality control practices of honey production operations. Environ Toxicol Chem 2020;39:1894–1907. © 2020 SETAC